2022
DOI: 10.2490/prm.20220043
|View full text |Cite
|
Sign up to set email alerts
|

Development of Cut-off Values on the Berg Balance Scale for Predicting Walking Independence in Older Adults with Hip Fracture

Abstract: Objectives: The aim of the current study was to identify a cut-off value for predicting walking independence at discharge in older adults with hip fracture based on their Berg Balance Scale (BBS) score at admission to a convalescent rehabilitation ward. Methods: This was a retrospective, multicenter, observational study of 187 older adults with hip fractures (mean age 83.7, range 66–97 years). Data was collected on the patients’ age, sex, treatment, and physical functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
1
0
Order By: Relevance
“…Considering the simplicity and ease of conducting the KUSBS, the KUSBS can replace the BBS to evaluate the standing balance of patients in inpatient rehabilitation facilities when the BBS is inadequate. Cohort studies conducted in inpatient rehabilitation settings [9][10][11][12][13]30,31] reported that the BBS at admission could predict walking ability at the time of discharge of patients with stroke [9][10][11]13,30,32] and hip fractures [12]. The hospital stays for patients with stroke in two previous studies was similar to those in our study, and the BBS cutoff values were 20 and 29 points [9,11].…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Considering the simplicity and ease of conducting the KUSBS, the KUSBS can replace the BBS to evaluate the standing balance of patients in inpatient rehabilitation facilities when the BBS is inadequate. Cohort studies conducted in inpatient rehabilitation settings [9][10][11][12][13]30,31] reported that the BBS at admission could predict walking ability at the time of discharge of patients with stroke [9][10][11]13,30,32] and hip fractures [12]. The hospital stays for patients with stroke in two previous studies was similar to those in our study, and the BBS cutoff values were 20 and 29 points [9,11].…”
Section: Discussionsupporting
confidence: 84%
“…In another study, the cutoff value for patients with hip fractures was 28 [12] while the mean participant age and duration of hospital stay were 84 years and 50 days, respectively. In our study, the cutoff values for patients with stroke were similar to those of young-old and old-old patients but different from those of oldestold patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment Indicators for Determining Walking Independence DOI: http://dx.doi.org/10.5772/intechopen.1003255 to rehabilitation wards is 18 points [10]. The BBS score of hip fracture patients admitted to rehabilitation wards helps to predict walking independence at discharge and determine treatment according to the predicted level of independence [14]. The reported cut-off value for the 10MWT, a walking indicator, for walking independence in patients in recovery wards is 0.8 m/s, indoor walking independence in older adults living in the community is 0.5 m/s, and outdoor walking independence is 1 m/s [11,12].…”
Section: Tablementioning
confidence: 99%
“…The effectiveness of rehabilitation can be assessed with clinical tests, the most popular of which are the Timed “Up and Go” test (TUG), the Dynamic Gait Index (DGI), the Berg Balance Scale (BBS), the Tinetti test (TT), and the Functional Reach test (FR) [ 9 , 10 , 11 , 12 ]. Clinical balance tests usually consist of static and dynamic tasks, while some even attempt to estimate the risk of falls.…”
Section: Introductionmentioning
confidence: 99%